Perancangan Dan Pengujian Motor Induksi Tiga Fase Multi-Kutub - Bambang Sugiyantoro; T Haryono; Yahya Farqadain (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2012)
Three-phase induction motor is a motor type which is most often encountered in the household and in industry. This is due to the cheap price, easy maintenance and long age. One way to change the speed of three phase induction motor is by changing the number of poles.This research was conducted to determine the characteristic of three-phase induction motor when a change is done either by number of poles loaded and no-load.Characteristics of the motor which want to know are the rotor speed, slip, flow, power, and power factor when th number of stator poles varied.The study was conducted by modifying the number of poles three-phase induction motor squirrel cage. Motor induction of the results of modification has a the number of poles which can be changed so that the motor induction have the the number of poles 2, 4, 8 or 16. Characteristics of induction motor testing is done by changing the number of poles, and then the measurement is done on the velocity of the rotor speed, slip, flow, power, and power factor when th number of stator poles varied.The results showed that three-phase induction motor speed can be varied by changing the number of poles, but their work is less satisfactory in performance as demonstated by large slip of the induction motor, especially with 2 poles, 4 poles and 8 poles.